Factors Affecting Non Compliance with Exclusive Breastfeeding Among Mothers: A Survey at District Hospital Dadu - Alma Khalid, Suhail Aman, Irfan Jhatial, Washdev Talreja, Wajid Hussain, Sasui Wadho, Muhammad Parial Shahani, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: According to standard guideline for breastfeeding, t is mandatory to practice exclusive breastfeeding during the first six months of a baby's life to provide the finest physiological support for all neonates. In Pakistan there is visible underuse of exclusive breastfeeding among lactating mothers. This study aims to assess the variables affecting the non-compliance to exclusive breastfeeding among mothers at a district hospital in Pakistan. Materials and methods: A descriptive cross sectional study was conducted to in Pediatric OPD at the district hospital Dadu from January to June 2022, 162 breast feeding mothers were interviewed regarding their practice towards exclusive breast feeding. Results: We observed that only 29. 5% mothers practiced exclusive breast feeding. All the mothers in the study had a breastfeeding child. Most of the mothers in this study were aged between 20 to 40 years (62%). The most common reason for non-compliance with the exclusive breastfeeding was the use of formula milk by the mothers. Conclusion: Inclination to use formula milk, insufficient breast milk, early weaning and lack of the education among mothers were most common causes of non-compliance towards exclusive breastfeeding. Mass level health education for maternal and child health are recommended. Keywords Breast feeding, Exclusive breastfeeding, Neonate, Maternal factors,